Pulsed transport critical currents of Bi2212 tapes in pulsed magnetic fields - Rogacki, K; Gilewski, A; Newson, M; Jones, H; Glowacki, B; Klamut, J (2002)
If high-TC superconductors are ever to be used in high-field applications, it is vital that the critical surfaces can be mapped under high-field conditions. However, the latest superconductors have high currents even at fields over 20 T, making accurate measurements very difficult due to the thermal and mechanical problems. In this paper, we compare measurements on BSCCO-2212 tape using a number of different methods, particularly an innovative pulsed transport current and pulsed field mode. We show how the analysis of the voltage signal from BSCCO-2212 tape in pulsed conditions may be used to extract the critical current in quasi-stationary conditions. The effect of a metallic substrate on the results is also briefly discussed.